A High‐Performance, Low‐Tortuosity Wood‐Carbon Monolith Reactor. Issue 2 (7th November 2016) - Wang, Yangang; Sun, Guanwu; Dai, Jiaqi; Chen, Guang; Morgenstern, Joe; Wang, Yanbin; Kang, Shifei; Zhu, Mingwei; Das, Siddhartha; Cui, Lifeng; Hu, Liangbing
Abstract : A highly efficient 3D wood‐derived carbon monolith reactor with a low tortuosity is demonstrated for high‐temperature reaction applications, using catalytic steam reforming of biomass tar as the model system. Outstanding catalytic activity is achieved as the reactant gases flow through this 3D natural wood‐derived catalyst, where over 99% toluene conversion and good stability at 700 °C are observed.